PENGARUH PENGGUNAAN LEMBAR KERJA MAHASISWA BERBASIS KONSEP DALAM PERKULIAHAN ANALISIS VEKTOR PROGRAM STUDI PENDIDIKAN MATEMATIKA - Puguh Wahyu Prasetyo; Fariz Setyawan; Sumargiyani Sumargiyani (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2018)
Vector analysis is one of the cource listed in the curriculum of the Mathematics Education Department, Faculty of Education and Teacher Traning, Universitas Ahmad Dahlan. One of the factors which cause any difficulties and problems in learning Vector Analysis is the student literature used by almost all of the students. That student literature explained a ressume of materials in a brief way completed with many practises., thatâ€™s why, the student literature seems too mechanistics. Many student can not use it by theirselves, they need guidances to read that book. In order to solve that problem, teacher designed a student worksheet which is used by the students of the Vector Analysis course when the class is runing. The design of the student worksheet is a concept-based designed. The students can investigate some formulas during the learning of Vector Analysis by theirselves. On the other hand, students can solve some practises contained in the student worksheet easier since the practises is completed with the intructions step by step. During the cource of Vector Analysis, the given student worksheet has a positive response from the student based on the quetionnaire taken from the students. Around 69,2% of the students give their positive response to the student worksheet. The mean of the students score also increased from 60,3 to 80,1. This shows that using the student worksheet in Vector Analysis cource was very useful.Â